International forestry cooperation: which way now ? - Kiekens, J. P.; Byron, R.N. (1997)
Although the international forestry dialogue has improved significantly since the Earth Summit, much remains to be done if sustainable forestry management is to be implemented on a global scale. This article discusses current trends: frequent, lengthy talks with limited action; declining official development assistance to forestry; an incomplete and incoherent international institutional framework; and increased reliance on hypothetical market-based mechanisms such as certification. It concludes that most progress towards worldwide forest sustainability will depend on good governance at the national and international level. Countries need to design and implement policies to address underlying causes of forest degradation and loss, both within and outside the forestry sector. An international framework that is truly conducive to sustainable forestry must be shaped through far-reaching reforms, such as strengthening development aid to forestry, adopting operational means of international forestry cooperation, reforming international forestry institutions and adopting a supportive legal framework.